Indeks Kepuasan Masyarakat Atas Pelayanan Publik Jalan Provinsi Pada Wilayah Kerja Pembangunan (WKP) III Pandeglang-Lebak - Arlan Marzan; Isvan Taufik; Zainul Hakim; Karvina Budiwati Apriliani; Agus Lukman Hakim; Hanifah (Program Studi Administrasi Negara Universitas Serang Raya, 2024)
The aim of this research is to analyze the results of the community satisfaction index survey regarding provincial road public services in the Pandeglang-Lebak III development work area (WKP). This research was analyzed quantitatively descriptively. The sampling technique used was purposive sampling with a combination of accidental sampling techniques, the number of samples using the Lemeshow formula with a total of 196 respondents using provincial roads. The research methods used are the Importance Performance Analysis (IPA) and Customer Statistics Index (CSI) methods. The results of the research show that the Importance Performance Analysis (IPA) method obtained results from 32 questions, of which 3 questions were in quadrant I (High Importance, Low Satisfaction), while 16 questions were in quadrant II (High Importance, High Satisfaction), while 9 questions were is in quadrant III (Low Importance, Low Satisfaction) and there are 4 questions in quadrant IV (Low Importance, High Satisfaction). The results of the Customer Statistics Index (CSI) analysis obtained a CSI result of 83.25%. This shows that people using provincial roads in the Pandeglang-Lebak III development work area (WKP) are in the Good criteria. based on the criteria in the interpretation in PERMENPAN RB No. 14 of 2017.